Analysis of the Use of the Parque Estadual do Monge, Lapa/PR - Meira Micaloski, Mariana (2021)
The use of a conservation unit is characterized as how visitors use these areas. The activities resulting from the use of provoking positive effects in the socioeconomic sphere; however, without control and monitoring mechanisms they can provide negative impacts to the environment. Given this context, the objective of the study was to conduct a data survey on the current situation of use of the Monge State Park, located in the municipality of Lapa, ParanaÌ. The collection of information was done using a questionnaire to the unit manager. The data on visitation, for the years 2012 to 2016, were obtained through the Instituto de AÌgua e Terra do ParanaÌ. The results showed an increasing visitation rate over the years, but no more specific data on the profile of these visitors and their satisfaction was available. There was a need to improve the park's infrastructure and signage, as well as to implement the sub-programs for use foreseen in the management plan. In this sense, attention to these parameters is recommended for the management of the unit, so that visitation can be enhanced strategically, stimulating social participation, to guarantee the objectives of creating the Monge State Park.